The future of money: cryptocurrency is the way to go in Malaysia / Dr. Zuraidah Mohamed Isa, Dr. Dahlia Ibrahim and Dr. Mohamad Hanif Abu Hassan - Mohamed Isa, Zuraidah; Ibrahim, Dahlia; Abu Hassan, Mohamad Hanif (Universiti Teknologi MARA, Kedah, 2022)
Digital currencies are sophisticated trading instruments that use blockchain technology and encryption to facilitate private and secure transactions. They are, to put it simply, very modern forms of electronic money. Despite a few cycles of digital currencies over the years, it was in the late 2000s that Bitcoin made a substantial contribution to their growth. There are other new cryptographic payment mechanisms available at the moment, but Bitcoin is by far the most wellknown, with Ethereum a close second. Cryptocurrencies are digital and virtual currencies supported by cryptographic techniques that enable secure online payment systems without the involvement of middlemen such as RENTAS or Duit Now, which are currently employed in online instant transfer systems. Since its inception in 2009, cryptocurrency is now available in over 20,000 different types. The most valuable cryptocurrency is Bitcoin; however despite its prominence, the market is abound with thousands of cryptocurrencies. Each cryptocurrency claims a unique function and specification, with Bitcoin being the most widely traded cryptocurrency. Cryptocurrency uses complex coding, including encryption, to validate transactions. Blockchain technology is tough to hack because of its nature as a more secure method of payment. According to Narayanan et. Al (2016), digital money is a combination of cryptography and money, with the "use of cryptography providing a component to safely embed the principles of a digital money framework within the framework itself." Cryptocurrency is a system that uses computers to mine it, where mining requires the solution of several mathematical algorithms. As a result, the algorithms are incomprehensible to the vast majority of hackers. During the 117th Muzakarah Majlis Kebangsaan Bagi Hal Ehwal Ugama Islam, the respective board concluded that cryptocurrency is allowed under Islamic law. The Mufti of Perak's office even issued statements on the digital money or cryptocurrency problem. This issue has sparked debate, or Muzakarah, among Malaysian scholars. The Perak Mufti Department (2022) concurred with the 117th Muzakarah Majlis Kebangsaan Bagi Hal Ehwal Ugama Islam, which stated that the law for digital currency transactions or any form of it is permissive (Harus).